Computers in personnel management: A South African survey - D. Tromp; T. Wegner (South African Journal of Business Management, 1986)
The personnel function currently faces many challenges and threats. Not the least of these is the growing erosion of its status at the strategic management level. The absence of a sound technological foundation is one of the contributory factors. The authors examine the contribution that computer-based personnel information systems are making towards the rectification of this problem. The availability of current computer-based decision aids is identified as well as the extent to which this technology is integrated within the personnel function in South African organizations.Die personeelfunksie staar tans heelwat veranderinge en uitdagings in die gesig. 'n Groot bedreiging is byvoorbeeld die toenemende afname in status op die strategiese bestuursvlak. Die afwesigheid van deeglikgefundeerde tegnologie is slegs een van die bydraende faktore. Hierdie artikel ondersoek die bydrae wat rekenaargefundeerde personeel-inligtingstelsels tot die regstelling van die probleem maak. Die beskikbaarheid van hedendaagse rekenaargefundeerde hulpmiddels vir besluitneming word geidentifiseer, tesame met 'n aanduiding van die mate waartoe hierdie tegnologie geintegreer word in die personeelfunksie in Suid Afrikaanse organisasies.
Keywords: 650